THE LEVITE'S CONCUBINE BASED ON JUDGES 19: Constructing a Hermeneutics of Meaning for Victim or Survivors of Sexual Violence - Duell, Angelina (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2023)
This paper offers a hermeneutics of meaning developed for victims or survivors of sexual violence in the parish context, focused primarily on Judges 19 and its ramifications in Judges 20–21. I construct this hermeneutic through an exegesis of Judges 19, based on feminist commentaries that tease out entry points for discussion with victim survivors. Using an imagined community Bible study, i construct a hermeneutic of meaning based on reconciliation and action using the work of pastoral theologians Carrie Doehring, Al Miles, and Monica A. Coleman.